2013
DOI: 10.3174/ajnr.a3665
|View full text |Cite
|
Sign up to set email alerts
|

Visual-Statistical Interpretation of 18F-FDG-PET Images for Characteristic Alzheimer Patterns in a Multicenter Study: Inter-Rater Concordance and Relationship to Automated Quantitative Evaluation

Abstract: EBM 2 ABSTRACT BACKGROUND AND PURPOSE:The role of 18 F-FDG-PET in the diagnosis of Alzheimer disease is increasing and should be validated. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…Furthermore, oxidative stress is well accepted as a key pathological event that contributes to AD pathogenesis, and is closely linked to induction of neuroinflammation in AD [6568]. For instance, a number of studies have found that increased ROS accumulation within mitochondria can feedback and facilitate mitochondrial dysfunction, leading to structural damage to the electron transfer chain and resultant ATP synthesis failure [6971]. In fact, impaired oxidative phosphorylation and decreased ATP generation have been observed in the brains of AD patients, and is viewed as a sensitive index for monitoring cognitive alteration in AD progression [7274].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, oxidative stress is well accepted as a key pathological event that contributes to AD pathogenesis, and is closely linked to induction of neuroinflammation in AD [6568]. For instance, a number of studies have found that increased ROS accumulation within mitochondria can feedback and facilitate mitochondrial dysfunction, leading to structural damage to the electron transfer chain and resultant ATP synthesis failure [6971]. In fact, impaired oxidative phosphorylation and decreased ATP generation have been observed in the brains of AD patients, and is viewed as a sensitive index for monitoring cognitive alteration in AD progression [7274].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, oxidative imbalance leading to a buildup of damaging oxidative byproducts has been consistently reported in AD progression, even at the early stage before significant senile plaques have formed [1921]. Furthermore, ROS accumulation in mitochondria causes a subsequent destruction of the electron transfer chain that leads to metabolic energy failure and mitochondrial dysfunction [2224], which have a well-documented role in AD pathology [25, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…Neuronal mitochondrial dysfunction is an early and prominent feature of AD (Wang 2009) as is reduced energy metabolism in the AD brain (Landau 2011, Shokouhi 2013, Yamane 2013). Diminished neuronal expression of genes encoding subunits of the ETC, as well as decreased expression or activity of many enzymes involved in oxidative metabolism, are also well-documented in AD brains (Cottrell 2001, Gibson 1998, Nagy 1999, Parker 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This system is being used as a standard procedure for all PET imaging in Japan. More than 60% of participants in 28 clinical sites were scanned by FDG-PET, and an in-depth analysis of the multicenter data has started [68][69][70]. Amyloid PET imaging using Pittsburgh Compound B ( 11 C-PiB) was conducted in w15 sites; whereas two sites performed PET studies using 11 C-BF-227.…”
Section: Japanese Adnimentioning
confidence: 99%